Matołek Broda. Przygody twórczo-wydawnicze - Staroń, Justyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article discusses issues related to the creative process and the editorial fate of The Adventures of Matołek the Billy-Goat by Kornel Makuszyński. It contains collected informations on the appearance of an idea for a book-comic for children (as told by Makuszyński’s wife – Janina, Marian Walentynowicz, Jan Gebethner), through the actual process of writing, the first edition and post-war issue. Also it discusses drawings from The 120 adventures of Matołek the Billy-Goat which sometimes differ quite significantly depending on the edition.